MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, KERJASAMA, DAN HASIL BELAJAR PADA MUATAN PPKN DENGAN MENGGUNAKAN MODEL BERPIKIR DI KELAS IV SDN ALALAK UTARA 2 - Akhmad, Lotfhi; Aslamiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem underlying this study is the low level of critical thinking skills, collaboration skills, and learning outcomes of students in Civic Education. This condition is caused by one-way learning processes, the lack of critical thinking activities, and the presentation of material that is overly theoretical, making students easily bored. To overcome these issues, this research applied the BERPIKIR learning model, which emphasizes the development of students’ activity, skills, and learning outcomes. This study employed Classroom Action Research (CAR) conducted in two cycles with four meetings. The research subjects were 25 fourth-grade students of SDN Alalak Utara 2. Data were collected through observation, written evaluation, and documentation, and analyzed using both qualitative and quantitative descriptive approaches. The indicators observed included teacher activity, student activity, critical thinking skills, collaboration skills, and learning outcomes. The results showed significant improvements across all aspects measured. Critical thinking skills from 49% to 83%, collaboration skills from 39% to 82%, and learning outcomes from 48% to 80%. These findings demonstrate that the BERPIKIR learning model is effective in improving the quality of Civic Education learning. Therefore, the BERPIKIR model is recommended as an alternative innovative learning strategy for teachers, principals, and future researchers to create more interactive and meaningful learning processes, ultimately supporting the improvement of education quality in primary schools.